HUCBC Treatment Improves Cognitive Outcome in Rats With Vascular Dementia - Venkat, Poornima; Culmone, Lauren; Chopp, Michael; Landschoot-Ward, Julie; Wang, Fengjie; Zacharek, Alex; Chen, Jieli (Frontiers in Aging Neuroscience, 2020)
Background and purpose: Vascular dementia (VaD) is the second leading form of dementia after Alzheimer’s disease (AD) and accounts for nearly 20% of all dementia. Yet, there are no FDA approved drugs specifically for VaD. We employed a multiple microinfarction (MMI) model of VaD in rats and tested the therapeutic effects of human umbilical cord blood cells (HUCBC) treatment on cognitive outcome, white matter (WM) integrity and glymphatic function. Methods: Male, retired breeder rats were subjected to the MMI model, and 3d later were treated with PBS or HUCBC (5×106, i.v.). Sham rats were included as naïve control. Cognitive tests were conducted, and rats were sacrificed at 28d after MMI. To evaluate glymphatic function, tracers (Texas Red dextran, MW: 3 kD and FITC-dextran, MW: 500 kD) were injected into the cisterna magna over 30min at 14d after MMI. Rats (3-4/group/time point) were sacrificed at 30min, 3h, and 6h and tracer movement analyzed using laser scanning confocal microscopy. Results: Compared to control MMI rats, HUCBC treated MMI rats exhibit significantly improved short-term memory and long-term memory indicated by increased discrimination index in novel object recognition task with retention delay of 4h and novel odor test with retention delay of 24h, respectively. HUCBC treatment also improves spatial learning and memory as measured using the Morris water maze test compared to control MMI rats. HUCBC treatment significantly increases axon and myelin density, increases oligodendrocyte and oligodendrocyte progenitor cell number, and increases Synaptophysin expression in the brain compared to control MMI rats. HUCBC treatment of MMI in rats significantly improves glymphatic function by reversing MMI induced delay in cerebrospinal fluid penetration and clearance from brain parenchyma via paravascular pathways. HUCBC treatment significantly increases miR-126 expression in serum, aquaporin-4 (AQP4) expression around cerebral vessels and decreases transforming growth factor (TGF-β) protein expression in brain which may contribute to HUCBC induced improved glymphatic function. Conclusions: HUCBC treatment of an MMI rat model of VaD promotes WM remodeling and improves glymphatic function which in concert may contribute to the improvement in cognition and memory. Thus, HUCBC treatment warrants further investigation as a potential therapy for VaD.